Scenarios of photovoltaic grid parity in colombia (2014)
In this article, we determined the residential Photovoltaic Grid Parity in 11 Colombian cities, by comparing grid energy prices offered by the local companies and the photovoltaic microgeneration cost for an average household. In order to do that, we developed a financial model, which considers the initial investment, cost of battery replacement, efficiency loss of photovoltaic technology and discount rate, among other variables, to determine the solar technology investment feasibility. It was found, in the base scenario, that on 2014 most of the considered cities have reached grid parity, while three of them will reach it between 2015 and 2021. Other scenarios, which consider higher discount rate, higher initial investment and slower learning curves, show similar results, where most cities will reach the grid parity before of 2028.